Conscientiousness in the Workplace: Evidence from a Field Experiment in West Africa - Allemand, Mathias; Kirchberger, Martina; Milusheva, Sveta; Newman, Carol; Roberts, Brent W.; Thorne, Vincent (The Review of Economics and Statistics, 2025)
Abstract Despite extensive evidence on the importance of non-cognitive skills for labor market outcomes, to what extent training can affect specific skills in adulthood remains an open question. We conducted a randomized controlled trial with low-skilled employed workers in Senegal where workers were randomly assigned to receive a training intervention designed to affect conscientiousness-related skills. We found that treated workers were significantly more likely to stay in their job, had higher earnings and better performance grades post intervention. Our findings suggest that non-cognitive skills can be affected later in the life cycle and targeted training can have substantial labor market returns.